Pengaruh pemberian edukasi gizi menggunakan media podcast terhadap peningkatan pengetahuan dan sikap mengenai obesitas pada remaja - Aisyah Fajrin Muthmainnah; Nur Setiawati Rahayu; Izna Nurdianty Muhdar (UHAMKA PRESS, 2021)
Obesity is a nutritional problem in adolescents nowadays. Obesity can increase risk of non-communicable diseases such as hypertension, cardiovascular disease, diabetes mellitus, cancer, osteoporosis and others which have implications for decreasing productivity and life expectancy. One factor of obesity is the lack of knowledge and information related obesity. Therefore, nutrition education using media that has been close to adolescents must be utilized in order to prevent obesity in adolescents. This research was a quasy experimental study with a non-equivalent control group design in 68 X-grade Labschool Kebayoran teenagers. Subjects were divided into 2 groups: 34 subjects as experimental group and 34 subjects as control group. In the experimental group podcasts and booklets were given for 1 week. Whereas, the control group was given a booklet without podcasts. Knowledge and attitude data related to balanced nutrition messages about obesity in adolescents were obtained from primary data in the form of questionnaires. The results of the study showed that there was influence of increased knowledge in the experimental group and the control group. There was an effect of increasing attitude in the experimental group and the control group. Meanwhile, there was difference in the effect of the experimental group with the control group on knowledge but there was no difference in the effect of the experimental group with the control group on attitudes. As conclusion that both the podcast and booklet media and without the podcast media related balanced nutrition messages about obesity in adolescents can improve knowledge and attitudes. Therefore, podcasts and booklets are considered as an effective media in providing nutrition education for balanced nutrition messages about obesity in adolescents.